In Vitro Differentiation of Myoblast Cells on Sheep Omentum Scaffold to Mature Myofibers - Khirallah , Ahmed; Hussein, Bahaa (University of Thi-Qar Journal of agricultural research, 2024)
The study aimed to engineer skeletal muscle tissue by used in vitro myoblast seeding on scaffolds to construct skeletal muscle tissue. Consequently, a scaffold made of sheep omentum and myoblast cells from rabbits was created for the healing of bodily tissues. Decellularization, mechanical testing, scanning electron microscopy (SEM) were used to analyze the structural features, and exposure to 25/Kg gamma radiation for sterilization. A seven-day-old male rabbit’s thigh muscle was successfully used to extract myoblasts, which were then subjected to a purity test utilizing flow cytometric analysis. After being seeded onto a scaffold, myoblasts were cultured in vitro for five days. This naturally derived collagen-based scaffold showed tremendous potential for in vitro skeletal muscle cultivation, which can be used as a substrate for filling wound beds or delivering cells. The in vitro finding of myoblast-seeded omentum scaffold suggested that myoblast harvested from primary culture are able to form myotube on scaffold.